POTENSI BIOGAS MELALUI PEMANFAATAN LIMBAH PADAT PADA PETERNAKAN SAPI PERAH BANGKA BOTANICAL GARDEN PANGKALPINANG - Widyastuti, Fianda Revina; Purwanto, Purwanto; Hadiyanto, Hadiyanto (Universitas Diponegoro, 2013)
Abstract At integrated farming areas Bangka Botanical Garden Pangkalpinang treating some of solid waste mixed with biogas digester will be used as fuel gas stove. Existing conditions in the dairy cattle by using the solid waste with 132 kg / day means at least they still used solid waste of 5 cows, so the biogas produced only 1 m3 / day. This paper is studyng about the energy’s need, economic and environments aspec in solid waste treatment to biogas and also about biogas management to provides the electricity need in the BBG Farm. The study is descriptive. The data have been taken from observation, measurement and interview with the farmer as the informan. Biogas produced can be used as lighting 60-100 watts for 50 hours, the driving source of energy 1 PK for 17 hours, producing 39 kWh electric energy and be able to cook 3 dishes for 40-48 servings. To produce 39.48 kWh / day, it can be used as a source of electrical energy BBG farm that has 35 lights with 25 watts of power which is lit for 12 hours / day. Up for lighting requires 10 kWh / day. For milking machine with 0.55 watts power usage requires 1.1 watts 2 times the rest can be used as a motor to move the water pump, lawn mower and activity classification. The BBG Farm need to increase the efficiency of utilization of biogas digester or biodigester everaging 1 unit abandoned and improve lighting installation connection using biogas. Keywords: biogas,cattle, energy,potential.